Le week-end [videorecording (DVD)] - Kureishi, Hanif; Broadbent, Jim; Duncan, Lindsay; Goldblum, Jeff, 1952-; Alexander, Olly, 1990-; Davis, Judith
Long-married British couple Nick and Meg are revisiting Paris for the first time since their honeymoon in an attempt to rekindle their relationship. Diffident, wistful Nick and demanding, take-charge Meg careen from harmony to disharmony as they take stock of half a lifetime of deep tenderness, and even deeper regret. An invitation from Nick's old friend Morgan, an amusingly eccentric American academic, soon leads them to a hopeful vision of what their marriage might still become.